2009
DOI: 10.1292/jvms.001377
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Whooper Swans (Cygnus cygnus) Infected with H5N1 Avian Influenza Virus in Akita, Japan, in 2008

Abstract: ABSTRACT. Two (1 adult and 1 young bird) of 4 H5N1-highly-pathogenic-avian-influenza (HPAI)-virus-infected whooper swans in Akita, Japan, in 2008 were investigated pathologically. Macroscopically, white spots with hemorrhages were scattered in the pancreas in the adult bird. Histologically, the adult bird had severe necrotizing pancreatitis and mild nonpurulent encephalitis. The young bird had severe nonpurulent encephalitis and nonpurulent enteric ganglionitis, and intestinal venous wall thickening. Virus ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…The findings are also in accordance with natural infection of tufted ducks with clade 2.2 virus (Bröjer et al, 2009) and clade 2.3.3 virus (Abdo et al, 2014). Lesions are also comparable to those seen in whooper swans (Ogawa et al, 2009;Okamatsu et al, 2010) and in ruddy shelducks and bar-headed geese experimentally infected with clade 2.3.2HPAI-H5N1 virus (A/bar-headed goose/ Mongolia/X53/2009) (Nemeth et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The findings are also in accordance with natural infection of tufted ducks with clade 2.2 virus (Bröjer et al, 2009) and clade 2.3.3 virus (Abdo et al, 2014). Lesions are also comparable to those seen in whooper swans (Ogawa et al, 2009;Okamatsu et al, 2010) and in ruddy shelducks and bar-headed geese experimentally infected with clade 2.3.2HPAI-H5N1 virus (A/bar-headed goose/ Mongolia/X53/2009) (Nemeth et al, 2013).…”
Section: Discussionsupporting
confidence: 83%
“…Studies in naturally infected whooper swans (Cygnus cygnus) (Ogawa et al, 2009;Okamatsu et al, 2010) in Japan as well as experimentally infected domestic ducks , ruddy shelducks (Tadorna ferruginea) and bar-headed geese (Nemeth et al, 2013) showed that the clade 2.3.2 viruses are highly pathogenic in wild birds. On the other hand, other data suggest that some of the clade 2.3.2 viruses are not as highly pathogenic since they were demonstrated in apparently healthy ducks (Kajihara et al, 2011;Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These lesions were found in all examined mute swans (15/15). Same results were obtained in mute swans naturally and experimentally infected with AIV H5N1 [6][7][8][9][10]. In contrast, there were no visible macroscopic lesions in the pancreas of infected hens.…”
Section: Resultssupporting
confidence: 75%
“…showed high mortality by infection with HPAIV [10]. There are few reports on the pathology of swans naturally infected with H5N1 HPAIV [11,12].…”
Section: Introductionmentioning
confidence: 99%